Deciphering the Impact of Mutations on the Binding Efficacy of SARS-CoV-2 Omicron and Delta Variants With Human ACE2 Receptor - Khan, Alamgir; Khan, Salman Ali; Zia, Komal; Altowyan, Mezna Saleh; Barakat, Assem; Ul-Haq, Zaheer (Frontiers in Chemistry, 2022)
The pandemic of COVID-19, caused by SARS-CoV-2 has globally affected the human health and economy. Since the emergence of novel corona virus SARS-CoV-2, the life-threatening virus continue to mutate and evolve. Irrespective of acquired natural immunity and vaccine-induced immunity, the emerging multiple variants are growing exponentially, crossing the territorial barriers of modern world. The rapid emergence of SARS-CoV-2 multiple variants challenges global researchers regarding efficacy of available vaccines and variants transmissibility. SARS-CoV-2 Surface-anchored S protein recognizes and interact with the host cell ACE2, facilitating viral adherence and entrance into the cell. Understanding the interfacial interactions between Spike protein of SARS-CoV-2 variants and human ACE2 receptor, is important for the design and development of antiviral therapeutics against SARS-CoV-2 emerging variants. Despite extensive research, the crucial determinants related to the molecular interactions between Spike protein of SARS-CoV-2 variants and host receptor are poorly understood. Thus, in this study, we explore the comparative interfacial binding pattern of SARS-CoV-2 Spike RBD of Wild Type, Delta and Omicron with human ACE2 receptor to determine the crucial determinants at atomistic level, using MD simulation and MM/GBSA energy calculations. Based on our findings, the substitution Q493R, G496S, Q498R, and Y505H induced internal conformational changes in Omicron Spike RBD, which leads to higher binding affinity than Delta Spike RBD with the human ACE2 receptor, eventually contributing higher transmission and infectivity. Taken together, these results could be used for the structure-based design of effective antiviral therapeutics again SARS-CoV-2 variants.